Bypassing hazard of housekeeping genes: their evaluation in rat granule neurons treated with cerebrospinal fluid of multiple sclerosis subjects - Mathur, Deepali; Lopez-Rodas, Gerardo; Ureña-Peralta, Juan; Casanova, Bonaventura; Coret-Ferrer, Francisco; Burgal-Marti, Maria (Frontiers in Cellular Neuroscience, 2015)
Gene expression studies employing real-time PCR has become an intrinsic part of biomedical research. Appropriate normalization of target gene transcript(s) based on stably expressed housekeeping genes is crucial in individual experimental conditions to obtain accurate results. In multiple sclerosis (MS), several gene expression studies have been undertaken, however, the suitability of housekeeping genes to express stably in this disease is not yet explored. Recent research suggests that their expression level may vary under different experimental conditions. Hence it is indispensible to evaluate their expression stability to accurately normalize target gene transcripts. The present study aims to evaluate the expression stability of seven housekeeping genes in rat granule neurons treated with cerebrospinal fluid of MS patients. The selected reference genes were quantified by real time PCR and their expression stability was assessed using GeNorm and NormFinder algorithms. Both methods reported transferrin receptor (Tfrc) and microglobulin beta-2 (B2m) the most stable genes whereas beta-actin (ActB) and glyceraldehyde-3-phosphate-dehydrogenase (Gapdh) the most fluctuated ones. Altogether our data demonstrate the significance of pre-validation of housekeeping genes for accurate normalization and indicates Tfrc and B2m as best endogenous controls in MS. ActB and Gapdh are not recommended in gene expression studies related to the current one.